睡眠障害および不定愁訴に対する鍼灸治療の1症例 - 渡邉, 勝之; 金野, 彰子 (人体科学, 2011)
Objective: We report a case of sleep disturbance and unidentified complaints that was improved by acupuncture and moxibustion therapy. Case: The patient was a woman in her 20s with sleep disturbance and unidentified complaints such as headache, general malaise, back pain and so on. The sleep disturbance had developed X-5 years previously when she got up early morning to go to work, in combination with stress and excessive desk work. This was accompanied by unidentified complaints. Because she experienced no improvement in symptoms on retiring, we commenced acupuncture and moxibustion therapy after the patient was referred by a doctor. Method of treatment: We administered acupuncture and moxibustion using the reactive point treatment protocol based on Primordial Oriental Medicine. We also advised her with good care such as using a hot-water bottle and taking light exercise. Evaluation method: The patient commented on changes in the symptoms of, sleep disturbance and we evaluated general malaise using a visual analogue scale (VAS). We measured the saliva oxidation reduction potential (ORP) as well as the activation of salivary α-amylase to evaluate general physical condition, and quality of life (QOL) was evaluated using the short form (SF)-8. We also evaluated changes in bilateral axillary temperature. Result: We found no changes in quantitative measurements. However, sleep disturbance was subjectively improved. Conclusion: The present case suggested that both acupuncture and moxibustion therapy and good care might be useful in sleep disturbance.